1996
DOI: 10.1172/jci118748
|View full text |Cite
|
Sign up to set email alerts
|

Expression of uncoupling protein in skeletal muscle and white fat of obese mice treated with thermogenic beta 3-adrenergic agonist.

Abstract: The mitochondrial uncoupling protein (UCP) is usually expressed only in brown adipose tissue (BAT) and a key molecule for metabolic thermogenesis. The effects of a highly selective ␤ 3-adrenergic agonist, CL316,243 (CL), on UCP expression in skeletal muscle and adipose tissues were examined in mice. Daily injection of CL (0.1 mg/kg, sc) to obese yellow KK mice for two weeks caused a significant reduction of body weight, associated with a marked decrease of white fat pad weight and hypertrophy of the interscapu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
124
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(140 citation statements)
references
References 23 publications
15
124
1
Order By: Relevance
“…The CL-treatment also resulted in about 3-fold increase in plasma free fatty acid level , and significant reduction of the plasma levels of glucose,insulin and T3 in obese mice. These effects of CL were essentially the same as those reported previously [17,24].…”
Section: Effects Of Cl-treatment On Tissue Weights and Blood Parameterssupporting
confidence: 90%
See 2 more Smart Citations
“…The CL-treatment also resulted in about 3-fold increase in plasma free fatty acid level , and significant reduction of the plasma levels of glucose,insulin and T3 in obese mice. These effects of CL were essentially the same as those reported previously [17,24].…”
Section: Effects Of Cl-treatment On Tissue Weights and Blood Parameterssupporting
confidence: 90%
“…UCP is originally known as a unique molecule exclusively present in brown adipose tissue (BAT), an organ for adaptive thermogenesis during cold exposure and spontaneous hyperphagia in rodents and some neonatal mammals including humans [9]. It has been demonstrated that chronic treatment of obese animals by agonist to the β3 adrenergic receptor (AR) resulted in a reduced adiposity associated with an increased expression of UCP [6,10,17,25]. Particularly interesting was that UCP was found in various fat pads usually considered as white adipose tissue (WAT) and even in skeletal muscle [6,17,25].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The publications of two papers in 1996 prompted several laboratories to search for mitochondrial UCP and/or UCP homologues in skeletal muscle and other tissues, namely, (i) the report by Nagase et al [34] claiming that treatment with a h3 agonist led to weight loss associated with expression of an uncoupling protein detected in skeletal muscle and white adipose tissue by Northern and Western probing for the BAT-UCP, and (ii) the report of Rolfe and Brand [35] that the phenomenon of mitochondrial dproton leakT is not unique to BAT, as originally thought, but also exists in tissues other than BAT, and could contribute as much as 25-50% of the liver and skeletal muscle heat production at rest.…”
Section: Novel Duncouplingt Proteinsmentioning
confidence: 99%
“…UCP-1 is specifically produced in BAT; this protein uncouples oxidative phosphorylation from electron transport, resulting in the dissipation of energy as heat [24,25]. The emergence of these ectopic cells in the WAT of rats [26] and of mice [27] was found to be induced by cold acclimatisation or by the administration of selective β3-AR agonists [27,28]. Interestingly, the emergence of brown fat cells in white fat depots was associated with a lean phenotype in several transgenic mouse models, including β1-AR transgenic mice [22], FOXC2 transgenic mice [29] and Tif2 −/− (also known as Ncoa2 −/− ) mice [30].…”
Section: Introductionmentioning
confidence: 99%